Caring for Critically Ill Children With Suspected or Proven Coronavirus Disease 2019 Infection: Recommendations by the Scientific Sections' Collaborative of the European Society of Pediatric and Neonatal Intensive Care*. Issue 1 (January 2021) - Rimensberger, Peter C.; Kneyber, Martin C. J.; Deep, Akash; Bansal, Mehak; Hoskote, Aparna; Javouhey, Etienne; Jourdain, Gilles; Latten, Lynne; MacLaren, Graeme; Morin, Luc; Pons-Odena, Marti; Ricci, Zaccaria; et al.
Abstract : Objectives: In children, coronavirus disease 2019 is usually mild but can develop severe hypoxemic failure or a severe multisystem inflammatory syndrome, the latter considered to be a postinfectious syndrome, with cardiac involvement alone or together with a toxic shock like-presentation. Given the novelty of severe acute respiratory syndrome coronavirus 2, the causative agent of the recent coronavirus disease 2019 pandemic, little is known about the pathophysiology and phenotypic expressions of this new infectious disease nor the optimal treatment approach. Study Selection: From inception to July 10, 2020, repeated PubMed and open Web searches have been done by the scientific section collaborative group members of the European Society of Pediatric and Neonatal Intensive Care. Data Extraction: There is little in the way of clinical research in children affected by coronavirus disease 2019, apart from descriptive data and epidemiology. Data Synthesis: Even though basic treatment and organ support considerations seem not to differ much from other critical illness, such as pediatric septic shock and multiple organ failure, seen in PICUs, some specific issues must be considered when caring for children with severe coronavirus disease 2019 disease. Conclusions: In this clinical guidance article, we review the current clinical knowledge of coronavirus disease 2019 disease in critically ill children and discuss some specific treatment concepts based mainly on expert opinion based on limited experience and the lack of any completed controlled trials in children at this time.